2016
DOI: 10.1016/j.chembiol.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Gene Expression Profiling Platform for Identification of Context-Dependent Drug Responses in Multicellular Tumor Spheroids

Abstract: Cancer cell lines grown as two-dimensional (2D) cultures have been an essential model for studying cancer biology and anticancer drug discovery. However, 2D cancer cell cultures have major limitations, as they do not closely mimic the heterogeneity and tissue context of in vivo tumors. Developing three-dimensional (3D) cell cultures, such as multicellular tumor spheroids, has the potential to address some of these limitations. Here, we combined a high-throughput gene expression profiling method with a tumor sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 41 publications
(51 reference statements)
3
44
0
Order By: Relevance
“…Although this is a small increment, it actually represents a potentially greater impact, since restricting proliferation by mitochondrial inhibitors is not apparent, or at least very modest in nutrient-rich cell culture conditions [31,32]. A recent study in HCT116 tumourspheres found that limiting activation of the mevalonate pathway enhanced the efficacy of mitochondrial inhibitors [39]. These findings, along with ours, indicate that limiting or targeting activated compensatory pathways could be a strategy to enhance the efficacy of mitochondrial inhibitors.…”
Section: Sbp Compensates For Effects Of Mitochondrial Inhibitor Npd2381supporting
confidence: 56%
“…Although this is a small increment, it actually represents a potentially greater impact, since restricting proliferation by mitochondrial inhibitors is not apparent, or at least very modest in nutrient-rich cell culture conditions [31,32]. A recent study in HCT116 tumourspheres found that limiting activation of the mevalonate pathway enhanced the efficacy of mitochondrial inhibitors [39]. These findings, along with ours, indicate that limiting or targeting activated compensatory pathways could be a strategy to enhance the efficacy of mitochondrial inhibitors.…”
Section: Sbp Compensates For Effects Of Mitochondrial Inhibitor Npd2381supporting
confidence: 56%
“…The possibility that defects in HN-protein maturation may also participate in thiazolide antiviral activity in SeV-infected cells is currently under investigation. In addition, it should be noted that nitazoxanide was found to inhibit oxidative phosphorylation leading to decreased ATP levels in cancer cells 28 , 29 . Since metabolic energy is known to be required for correct disulfide bond formation and folding of several proteins in the ER 30 32 , it is possible that lower ATP levels in NTZ-treated cells may contribute to F-protein misfolding in our model.…”
Section: Resultsmentioning
confidence: 99%
“…Several RNA-sequencing studies demonstrated significant, tumor-relevant molecular changes induced by 3D cell culture (12,22,23). Glioblastoma spheroids in 3D culture mimicked in vivo tissues, organs and even patient tumors, providing in vivo 34: 199-211 (2020) 204 similar cellular properties including hypoxic gradients, cellular heterogeneity with both slow-dividing cells and proliferative tumor bulk (24,25) and higher drug resistance (10).…”
Section: Discussionmentioning
confidence: 99%